Discovery of the worker caste and descriptions of two new species of Anomalomyrma (Hymenoptera: Formicidae: Leptanillinae) with unique abdominal morphology - Borowiec, Marek L.; Schulz, Andreas; Alpert, Gary D.; Baňař, Petr (Zootaxa, 2011)
The hitherto unknown worker caste of Anomalomyrma Taylor, 1990 is described for the first time. Two new species, Anomalomyrma boltoni n. sp. from Cameron Highlands, Peninsular Malaysia and Anomalomyrma helenae n. sp. from El Nido region of Palawan, Philippines, are described. In workers of both new species abdominal segments II and III (petiole and postpetiole) are rigidly fused together across both tergites and sternites. This is the first report of such fused abdominal morphology in worker Formicidae. Both new species lack a vertical lamella on the mandible, originally considered to be diagnostic for the genus and the main character separating Anomalomyrma from Protanilla Taylor, 1990. Modified generic diagnoses are proposed for both Anomalomyrma and Protanilla. Wing venation is described for the first time from an anomalomyrmine alate gyne, and prospects for the future of the nomenclature of the group's genera are discussed. A modified key to the genera of Leptanillinae is given along with a short note on the correct authorship of some leptanilline names.